Pengaruh Lama Perendaman Benih dalam Larutan CaCO3 terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) pada Media Tanaman yang Berbeda - Ericson, Gaol Uli Lumban; Sugiatno, Sugiatno; Edy, Akari; Susanto, Herry (Universitas Lampung, 2023)
The presence of pulp in cocoa seeds is known to inhibit seed germination and seedling growth. The conventional method of removing pulp from cocoa seeds is done mechanically by rubbing the seeds with rubbing ash. Conventional pulp removal has disadvantages, such as being less practical and potentially damaging the seed surface. Therefore, it is necessary to try chemically removing the pulp from cocoa seeds by soaking the seeds in a lime solution (CaCO3). This study aims to determine the effect of the duration of cocoa seed soaking in CaCO3 solution and different planting media compositions on seedling growth. The research was conducted from September to December 2021 at a plastic house in Labuhan Dalam Village, Tanjung Senang District, Bandar Lampung, and the Seed Laboratory, Faculty of Agriculture, University of Lampung, Gedong Meneng, Bandar Lampung. The study used a Completely Randomized Design (CRD) arranged in a factorial manner. The first factor was the duration of cocoa seed soaking in CaCO3 solution, consisting of no soaking, soaking for 30, 60, 120, and 240 minutes. The second factor was the planting media composition, consisting of a mixture of rice husk charcoal + manure, sand + manure, and sand + rice husk charcoal + manure. Each treatment combination was replicated three times, resulting in 45 experimental units. The observation data were analyzed using analysis of variance, and the mean differences were tested using the Least Significant Difference (LSD) test at the 5% level. The results of the study showed that the duration of cocoa seed soaking in CaCO3 solution had no effect on cocoa seedling growth. The planting media composition of sand + rice husk charcoal + manure had a significant effect on the best cocoa seedling growth compared to the planting media compositions of rice husk charcoal + manure and sand + manure. Soaking cocoa seeds in CaCO3 solution had no effect on cocoa seedling growth in different planting media. Keywords : Cocoa seeds, pulp, CaCO3, soaking, planting media